A Critical Analysis of al-Ḥiyal al-Syar'iyyah Concept within the Ḥanafī School Paradigm: Implications and Implementation in Contemporary Financial Transactions - Sartini Lambajo; Siti Sa’dianti; Nabilah Al Azizah; Sabila Adzkia (NUKHBATUL 'ULUM: Jurnal Bidang Kajian Islam, 2024)
This study examines the concept of al-ḥiyal al-syar'iyyah (permissible legal stratagems) from the Ḥanafī school of thought perspective and its application in contemporary financial transactions. The research aims to analyze the Ḥanafī scholars' views on al-ḥiyal al-syar'iyyah and explore its implementation in financial contracts (mu'āmalah māliyyah). Employing a qualitative approach with normative and sociological perspectives, this study focuses on textual analysis of classical and modern Islamic jurisprudence sources. The findings reveal that the Ḥanafī school considers al-ḥiyal al-syar'iyyah as a legitimate method to navigate religious matters without violating Islamic law, categorizing it into permissible and impermissible stratagems based on their objectives and alignment with maqāṣid al-sharī'ah (objectives of Islamic law). The study also demonstrates the application of this concept in various financial contracts, including sales, leases, loans, gifts, and contemporary Islamic financial products. This research contributes to the ongoing discourse on Islamic legal theory and its practical implications in modern Islamic finance, providing valuable insights for academics, policymakers, and practitioners in the field.